Effects of Schistosoma haematobium infection and treatment on the systemic and mucosal immune phenotype, gene expression and microbiome: A systematic review. - Anna M Mertelsmann; Sheridan F Bowers; Drew Wright; Jane K Maganga; Humphrey D Mazigo; Lishomwa C Ndhlovu; John M Changalucha; Jennifer A Downs (PLoS Neglected Tropical Diseases)
Background Urogenital schistosomiasis caused by Schistosoma haematobium affects approximately 110 million people globally, with the majority of cases in low- and middle-income countries. Schistosome infections have been shown to impact the host immune system, gene expression, and microbiome composition. Studies have demonstrated variations in pathology between schistosome subspecies. In the case of S. haematobium, infection has been associated with HIV acquisition and bladder cancer. However, the underlying pathophysiology has been understudied compared to other schistosome species. This systematic review comprehensively investigates and assimilates the effects of S. haematobium infection on systemic and local host mucosal immunity, cellular gene expression and microbiome. Methods We conducted a systematic review assessing the reported effects of S. haematobium infections and anthelmintic treatment on the immune system, gene expression and microbiome in humans and animal models. This review followed PRISMA guidelines and was registered prospectively in PROSPERO (CRD42022372607). Randomized clinical trials, cohort, cross-sectional, case-control, experimental ex vivo, and animal studies were included. Two reviewers performed screening independently. Results We screened 3,177 studies and included 94. S. haematobium was reported to lead to: (i) a mixed immune response with a predominant type 2 immune phenotype, increased T and B regulatory cells, and select pro-inflammatory cytokines; (ii) distinct molecular alterations that would compromise epithelial integrity, such as increased metalloproteinase expression, and promote immunological changes and cellular transformation, specifically upregulation of genes p53 and Bcl-2; and (iii) microbiome dysbiosis in the urinary, intestinal, and genital tracts. Conclusion S. haematobium induces distinct alterations in the host's immune system, molecular profile, and microbiome. This leads to a diverse range of inflammatory and anti-inflammatory responses and impaired integrity of the local mucosal epithelial barrier, elevating the risks of secondary infections. Further, S. haematobium promotes cellular transformation with oncogenic potential and disrupts the microbiome, further influencing the immune system and genetic makeup. Understanding the pathophysiology of these interactions can improve outcomes for the sequelae of this devastating parasitic infection.